Studi Literatur Perubahan Antara CISSP 10 Domain dengan 8 Domain - Michael Perkasa; Agustinus Noertjahyana; Silvia Rostianingsih (Jurnal Infra, 2016)
Degree is one that is being achieved by most people in their work, in order to influence the potential possessed by an employee or the employee. So with the development of technology, people increasingly need a degree or certification in order to hone and enhance its capabilities.With the changes under discussion on the differences of the 10 CISSP domains domain into 8 domains in each domain has the characteristics of each and their respective utility functions. CISSP 8 domain is a new domain that have updated their respective functions and become more efficient because fewer but more focused functions.Therefore, domain 8 is more favored than 10 domain due to factors such support.